2022
DOI: 10.1021/acsomega.2c00727
|View full text |Cite
|
Sign up to set email alerts
|

Histological Injury to Rat Brain, Liver, and Kidneys by Gold Nanoparticles is Dose-Dependent

Abstract: Gold nanoparticles (GNPs) possess various interesting plasmonic properties that can provide a variety of diagnostic and therapeutic functionalities for biomedical applications. Compared to other inorganic metal nanoparticles (NPs), GNPs are less toxic and more biocompatible. However, the in vivo toxicity of gold nanoparticles on humans can be significant due to the size effect. This work aims to study the effect of multiple doses of small-size (≈20 nm) GNPs on the vital organs of Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
2
3
0
Order By: Relevance
“…G3 injected with 20 nm GNPs clarified moderate atrophy of some renal tubules, moderate intertubular edema, and cystic dilation of others. This finding goes hand in hand with the finding of Fadia et al . (2022) who found massive congestive vessels, numerous lymphocyte infiltrations, tubular degeneration, and a necrotic condition in the 20 nm GNPs treated rat kidneys.…”
Section: Discussionsupporting
confidence: 57%
“…G3 injected with 20 nm GNPs clarified moderate atrophy of some renal tubules, moderate intertubular edema, and cystic dilation of others. This finding goes hand in hand with the finding of Fadia et al . (2022) who found massive congestive vessels, numerous lymphocyte infiltrations, tubular degeneration, and a necrotic condition in the 20 nm GNPs treated rat kidneys.…”
Section: Discussionsupporting
confidence: 57%
“…Meanwhile, the liver of G3 that injected intra peritoneal with GNPs in a dose of 20 nm showed moderate hydropic degeneration of the hepatocytes, moderate blood vessels dilatation with moderate congestions in portal triad, moderate periductal inflammatory cells infiltrations, with moderate inflammatory cells infiltrations in the portal triad surrounding portal blood vessels, moderate fibrous connective tissue proliferations of mostly collagen fibers surrounding the portal blood vessels with moderate sinusoidal dilatation & congestion in between the hepatocytes . These findings was in agreement with 46 who observed congestive vessel and dilated central vein in the rat liver after 20 nm treatment with GNPs, as well as lymphocyte infiltration, inflammation, and isolated regions of necrosis. Furthermore, recent investigation clarified cell necrosis and leukocyte infiltration in the hepatic parenchyma in group received 20 nm GNPs after 24 h of treatment 47 .…”
supporting
confidence: 93%
“…We found that over 99% of implanted HA particles irrespective of size (nHA or mHA) stayed locally within the defect up to 28 days, indicating the safety of HA particle usage especially in the bone. Previous studies have shown inorganic nanoparticles could induce pathological changes in vital organs ( Ferdous and Nemmar, 2020 ; Fadia et al, 2022 ). Nanoparticles that enter through the hepatic portal vein mostly reside in the liver due to the presence of leaky sinusoids and abundance of liver-resident cells with high endocytic or phagocytic activities ( Tsoi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%